(untitled) (Rivista italiana di Paleontologia e Stratigrafia, 2006)
Middle Triassic history of the Southern Bakony Mts. is outlined on the base of horizontal and vertical facies changes of the formations. During the Pelsonian (Balatonicus Chron) the evolution of the basins and platforms was determined basically by synsedimentary tectonics. The Felsõörs basin of the Balaton Highland opened due to the block-faulting of the Bithynian carbonate ramp (Megyehegy Dolomite). Above the drowning blocks „halfgraben” basins were formed (Felsõörs Formation), while isolated platforms developed on the uplifted ones in the middle part of the Balaton Highland and on the Veszprém plateau (Tagyon Formation). Due to the relative sea-level fall in the early Illyrian, the platforms became subaerially exposed and karstified. As a consequence of the late Illyrian tectonic subsidence (manifested by neptunian dykes) the central platform of the Balaton Highland has been drowned (Camunum Subchron). On the contrary, the Anisian platform of the Veszprém plateau was totally flooded only during the latest Illyrian (Reitzi Subchron) due to eustatic sea-level rise. It was followed by a short highstand period (Secedensis Chron), characterised by the first progradation of the Budaörs platform on the Veszprém plateau and highstand shedding in the basins and on the submarine high (Vászoly Limestone) in the centre of the Balaton Highland basin. Due to the following rapid sea-level rise, carbonate sedimentation continued in eupelagic basin from the Fassanian (Buchenstein Formation). At the beginning of the late Longobardian highstand period (Regoledanus Chron) the Budaörs platform intensively prograded from the Veszprém plateau to the southwest, causing highstand shedding in the Balaton Highland basin (Füred Limestone).